Alkaptonuria caused by compound heterozygote mutations - (:unkn) unknown (MEDECINE ET HYGIENE, 2003)
Alkaptonuria caused by compound heterozygote mutations: Alkaptonuria is a rare autosomal recessive disorder of inborn errors of metabolism. It is characterised by the deposition of much less than ochronotic pigment much greater than especially in connective tissue as a result of deficieny of the much less than homogentisic acid oxidase much greater than enzyme which has a role in the catabolism of tyrosine and phenylalanine. A compound heterozygote alkaptonuria patient, with manifestations In adulthood, without infantile and childhood signs is presented. The described alkaptonuria mutations are reported for the first time in the Turkish population.
Keywords: alkaptonuria; homogentisic acid; compound heterozygosity; OCHRONOSIS; ALCAPTONURIA; GENE